NAFERTISITE, A LAYER TITANOSILICATE MEMBER OF A POLYSOMATIC SERIES INCLUDING MICA - Ferraris G.; Ivaldi G.; Belluso E.; Khomyakov A.P.; Soboleva S.V.; Pavese A. (My University, 1996)
Nafertisite, (Na,K)(3)(Fe2+,Fe3+,square)(10)[Ti-2(Si,Fe3+,Al)(12)O-37](OH,O)(6), is an alkaline titanosilicate from the Khibina massif (Kola Peninsula, Russia). It is monoclinic A2/m with a = 5.353(4), b = 16.176(12), c = 21.95(2) Angstrom, beta = 94.6(2)degrees, Z = 2. The comparison with bafertisite, Ba-2(Fe,Mn)(4)[Ti2Si4O17](OH,O)(3), and astrophyllite, (K,Na)(3)(Fe,Mn)(7) [Ti2Si8O27](OH,O)(4), allowed to obtain a structural model for nafertisite which has been tested against X-ray has been tested diffraction data obtained from a very poor crystal. On the basis of bafertisite-like B module (A,square)(2)(M,square)(4) [X(2)T(4)O(17)](OH)(2) and a mica-like M module (A,square)(M,square)(3)[T4O10](OH)(2), a polysomatic series BM(n) can be defined where bafertisite, astrophyllite, nafertisite and mica are the members with n = 0, 1, 2, infinity, respectively. Its called heterophyllosilicate series because the crystal structures of the members consist of 2:1 HOH layers where O is an octahedral sheet and H is a tetrahedral-like sheet which differs from the T sheet of the phyllosilicates for the insertion of Ti octahedra; these play a role similar to that of Si tetrahedra. A group of titanosilicates is shown to be derivatives of the bafertisite structure with different interlayer contents.